Unilateral Renal Agenesis in a Bitch - Richter, Lara; Hromatka, Rosângela; Carvalho, Tatiane; Gueretz, Juliano Santos (Acta Scientiae Veterinariae, 2024)
Background: Nephropathies are generalizations that indicate kidney disease or injury, which eventually can lead to some type of kidney failure. A rare condition in dogs, renal agenesis can be bilateral or unilateral, the former being incompatible with postnatal life. Unilateral renal agenesis is commonly asymptomatic and is accompanied by hypertrophy of the remaining kidney. Ipsilateral ureteral agenesis may also be seen to the absent kidney, the ureter may be absent or malformed with a blunt end ending in connective tissue. The aim of this report is to describe a case of renal agenesis in an adult bitch. Case: An approximately 5-year-old spayed bitch mixed-breed, was seen for consultation and preoperative exams, in order to perform an elective periodontal cleaning procedure. The animal had a history of ovariosalpingohysterectomy without previous laboratory tests. Imaging tests were also performed. In the ultrasound examination, the absence of the right kidney was found, and the other organs had a normal appearance. A 2 nd ultrasound and radiography performed later showed the absence of a functional right kidney and its remains. In both exams, the left kidney was within an apparent normality. During the radiographic examination, no silhouette or structure consistent with the right kidney was observed. Discussion: The etiopathogenesis of renal agenesis in companion animals is still uncertain, but genetic predisposition has been identified mainly in Beagle dogs, as well as in Shetland Sheepdogs and Doberman Pinschers. In agreement with the present case report, the kidney should be retroperitoneally compressed against the dorsal abdominal wall, more cranial in relation to the left kidney, predominantly in the lumbar region, projecting cranially to the intrathoracic part of the abdo men. As renal function can be sustained when up to 75% of the organ is affected, unilateral agenesis can go unnoticed during the animal’s life, being found by chance in routine examinations or during necropsy. This is due in most cases to the compensatory hypertrophy of the other kidney, with an increase in the glomerular filtration rate, which explains why biochemical parameters of renal evaluation remain in the normal range. This also corroborates the present report, because although there was no compensatory hypertrophy of the left kidney, the diagnosis was only made in routine exams, that is, the patient had no clinical signs consistent with kidney disease. The study of nephrology in companion animals is of extreme clinical importance, because due to genetics or the prolongation of life of these individuals, dysfunctions and diseases related to the urinary system are increasingly present in the routine of care, in significant numbers and severity. Although unilateral renal agenesis is compatible with life, this dysfunction can lead to functional overload of the remaining kidney, which can lead to renal failure. In veterinary nephrology there is still room for discussion and learning and the way to develop better strategies to address this problem is through study and research in the area. It is extremely important to assess the health of the urinary system of companion animals, especially in preoperative exams, allowing for adequate care and procedures to maintain the patient’s health and good quality of life. Although the patient did not show clinical signs, knowledge of the pathology allowed a safer practice of anesthesia and the procedure in which she was submitted, in addition to providing more prophylactic care for the animal, so that the alteration does not evolve into a more serious disease. Keywords: congenital anomaly, nephrology, renal malformation. Título: Agenesia renal unilateral em uma cadela Descritores: anomalia congênita, malformação renal, nefrologia